(untitled) (Journal of Bangladesh Academy of Sciences, 2020)
Catalytic pyrolysis of waste plastics into liquid hydrocarbon was conducted in a locally-made stainless steel reactor. Mesoporous kaolin clay treated with sulfuric acid in the concentration range of 3-7 M was used as a catalyst and waste polyethylene was the plastic feed. The X-ray powder diffraction (XRPD) pattern showed that the raw kaolin clay is crystalline. However, XRPD patterns of H2SO4 acid treated kaolin and Ni and Ru metal impregnated H2SO4 treated kaolin did not exhibit any characteristic diffraction peaks of kaolin. The acid treatment of kaolin causes leaching of Al3+ and results in disintegration of layered structure of kaolin, leading to the formation of Al2(SO4)3, SiO2, and amorphous phase. After 5 M H2SO4 acid treatment, the content of Al2O3 decreased significantly to 18.62%. The Si/Al ratio and specific surface area were found to increase after 5 M sulfuric acid treatment from 1.79 to 3.48 and 6.85 m2/g to 17.92 m2/g, respectively. The nitrogen adsorption-desorption isotherms of the 5 M H2SO4 acid treated kaolin clay showed the isotherm to be of type IV typical for mesoporous structure. Among 3, 5, and 7 M H2SO4 treated kaolin catalysts, the 3 M H2SO4 treated kaolin (at a catalyst to plastic feed ratio of 1:5) exhibited the highest activity with the yield of 83% liquid hydrocarbon. The Ru- and Ni-impregnated 5 M H2SO4 treated kaolin catalyst provided 76% and 79% yield, respectively of liquid hydrocarbon at a catalyst to plastic ratio of 1:5. The gas chromatography-mass spectrometry (GC-MS), 1H NMR, and FTIR spectral analysis confirmed the presence of linear and branched alkanes and alkenes (C9-C20) in the end product obtained with 5 M H2SO4 treated kaolin catalyst. The produced liquid hydrocarbon was found to be free from aromatic compounds importantly polycyclic aromatic hydrocarbons which are potent mutagenic and carcinogenic. Journal of Bangladesh Academy of Sciences, Vol. 44, No. 1, 1-12, 2020